Comparison of Generation Z and Millennial Communication Styles on Social Media X in the Angry Community - Salsa Guspita; Maylanny Christin (Jurnal Komunikasi, 2025)
The rapid development of social media has shaped the dynamics of social communication, especially among Millennials and Generation Z. This study aims to interpret the communication styles of the two generations on the social media platform X (formerly Twitter), focusing on their interactions in the "Angry Community" which is a place for expressing emotions and social issues. Using a qualitative approach with a constructivist paradigm, this study explores how social reality is expressed and shaped through digital communication patterns. The results show significant differences in communication styles: members of the Angry Community from the Millennial Generation tend to adopt a more careful, systematic, and reflective communication style, emphasizing information verification and maintaining politeness. In contrast, Generation Z shows a more expressive, spontaneous, and informal communication style, often using slang, sarcasm, abbreviations, and emojis to voice complaints and share authentic experiences, although sometimes lacking verification. This study identifies that six dominant issues (such as economic inequality, social pressure, and job discrimination) are expressed with the distinctive communication styles of each generation, making the Angry Community a reflection of the complexity of digital expression and intergenerational interaction that also highlights structural problems in society.